Sadiria longistyla (Myrsinoideae, Primulaceae), a new species from Yunnan, China - Wang, Li-Yan; Wang, Ze-Huan; Chen, Li; Zhao, Fei; Li, Rong-Jia (Phytotaxa, 2018)
Sadiria longistyla from West Yunnan, China, is described as a species new to science and illustrated. It morphologically resembles S. eugenifolia var. burmanica, but differs by its fewer and larger leaves on the flowering branches, more lateral veins, larger inflorescences and petals, and smaller sepals. In addition, this new species is compared to S. aberrans, the only representative of Sadiria in China. A key to all taxa of Sadiria is also provided here.